2021
DOI: 10.3390/ijerph18052639
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Competences of the Professionals in Charge of Family Evidence-Based Programmes on Internalizing and Externalizing Symptoms in Adolescents

Abstract: This study analyses the influence of trainers' intrapersonal and group management competences on the effectiveness of the Universal Strengthening Families Program 11-14 (SFP 11-14). More specifically, it assesses the effect of these competences on internalizing and externalizing symptoms in adolescents. The analysed data is made up of ratings given by the 174 mothers participating in SFP 11-14. The results confirm the effectiveness of SFP 11-14 in reducing internalizing and externalizing symptoms in adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…In Orte, Sánchez-Prieto, Pascual, and Montaño (2021), it was shown that trainers with limited skills were associated with fewer changes in the symptomatology of children. In addition, in Orte, Sánchez-Prieto, Montaño, and Pascual (2021), the influence of trainers’ intrapersonal and interpersonal competences was demonstrated on internalizing symptoms in adolescents. For this reason, it is important to identify possible factors that might foster higher level skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Orte, Sánchez-Prieto, Pascual, and Montaño (2021), it was shown that trainers with limited skills were associated with fewer changes in the symptomatology of children. In addition, in Orte, Sánchez-Prieto, Montaño, and Pascual (2021), the influence of trainers’ intrapersonal and interpersonal competences was demonstrated on internalizing symptoms in adolescents. For this reason, it is important to identify possible factors that might foster higher level skills.…”
Section: Discussionmentioning
confidence: 99%
“…First, there must be prior training for EBP providers aimed at boosting their competences and attitudes to evidence-based practice. As explained, higher competence levels and conducive attitudes to evidence-based practice can influence the effectiveness of EBPs (Orte, Sánchez-Prieto, Montaño, & Pascual, 2021; Orte, Sánchez-Prieto, Pascual, & Montaño, 2021). Second, the program’s main objectives must be achieved by taking an educational focus.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…La elevada estructuración de los programas ofrece una serie de ventajas al profesional, como la seguridad de que aplica las pautas adecuadas y de que su actuación se vincula a los principales aspectos del programa (Ballester et al, 2020a). El problema principal radicaría en que la eficacia del programa puede verse comprometida si los formadores no respetan sus principios (Borntrager et al, 2009;Forehand et al, 2010;Orte et al 2021a). Además, un profesional de la formación, inevitablemente, aporta a su tarea un componente afectivo y actitudinal que transmite implícitamente o explícitamente a los participantes (García et al, 2009;Gairín, 2011).…”
Section: Formadores Del Programa De Competencia Familiar Universal 11-14unclassified
“…Como plantean Asgary-Eden y Leeso (2011), las habilidades y las competencias de los profesionales son variables que pueden influir sobre los resultados (Orte et al 2021a(Orte et al , 2021b. Para obtener favorecer la eficacia, el profesional debe contar con competencias intrapersonales e interpersonales, conocimientos específicos sobre la formación y estrategias metodológicas y pedagógicas, que le permitan gestionar las dinámicas de aprendizaje (UNDOC, 2015;Klimes-Dougan et al, 2009;Orte et al, 2021b;.…”
Section: Formadores Del Programa De Competencia Familiar Universal 11-14unclassified